2023
DOI: 10.1111/jvim.16713
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gallbladder motility assessed by ultrasonography in dogs with hyperlipidemia

Abstract: Background The pathogenesis of gallbladder (GB) mucoceles in dogs is unknown. It has been proposed that hyperlipidemia could impair GB motility and contribute to GB mucocele formation. Hypothesis/Objectives The objective of this study was to compare GB motility in dogs with hyperlipidemia to control dogs using ultrasonography. We hypothesized that hyperlipidemic dogs will have decreased GB motility compared with controls. Animals Twenty‐six hyperlipidemic and 28 healthy, age‐matched control dogs were prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…It has been found that patients with Hypothyroidism are more likely to develop CBDS due to impaired biliary emptying, while patients with Hyperthyroidism are at greater risk of developing stones due to increased cholesterol reabsorption and the presence of more cholesterol in the bile composition ( Ravi et al, 2023 ). Studies have also found that dogs with hyperlipidemia are more likely to develop gallbladder and liver related diseases due to decreased gallbladder motility ( Villm et al, 2023 ). The body regulates the biliary system through humoral hormones and other cytokines, including cholecystokinin (CCK), which stimulates gallbladder contraction and bile secretion, as well as GLP-2 and FGF19, which promote gallbladder relaxation ( Choi et al, 2006 ; Yusta et al, 2017 ; Metry et al, 2023 ).…”
Section: Mechanisms Of Gallstone Formationmentioning
confidence: 99%
“…It has been found that patients with Hypothyroidism are more likely to develop CBDS due to impaired biliary emptying, while patients with Hyperthyroidism are at greater risk of developing stones due to increased cholesterol reabsorption and the presence of more cholesterol in the bile composition ( Ravi et al, 2023 ). Studies have also found that dogs with hyperlipidemia are more likely to develop gallbladder and liver related diseases due to decreased gallbladder motility ( Villm et al, 2023 ). The body regulates the biliary system through humoral hormones and other cytokines, including cholecystokinin (CCK), which stimulates gallbladder contraction and bile secretion, as well as GLP-2 and FGF19, which promote gallbladder relaxation ( Choi et al, 2006 ; Yusta et al, 2017 ; Metry et al, 2023 ).…”
Section: Mechanisms Of Gallstone Formationmentioning
confidence: 99%